Analisis Pengaruh Ukuran Perusahaan, Profitabilitas, Leverage, Dan Kualitas Audit Terhadap Manajemen Laba. Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015 – 2019 - Supriadi, Holili; Hastuti, Wedia; Adhani, Ida (Accounting Research and Business Journal, 2024)
The purpose of this research is to ascertain whether the management of earnings by manufacturing businesses listed on the Indonesia Stock Exchange between 2015 and 2019 is influenced by company size, profitability, leverage, and audit quality. In this study, the following variables are employed: (1) Profit management is a dependent variable; and (2) company size, profitability, leverage, and audit quality are independent variables. Manufacturing companies that are listed on the Indonesian Stock Exchange are the subjects of this study. The research's data source was each company's annual or financial report from 2015 to 2019. The research sample consisted of 29 companies selected through the use of purposive sampling. Numerous tests, including the correlation and determination coefficient tests, autocorrelation test, multiple linear regression analysis, F-statistical test, t-statistical test, and multicollinearity test, were conducted as analytical tools using the Statistical Package for Social Sciences (SPSS) version 23 . The F-statistical test findings show a significant value of 0.000, or less than 0.05. Therefore, a company's size, profitability, leverage, and audit quality all together have a major influence on earnings management.